Conjugation-enhanced porous aromatic framework enables pore-confined photocatalytic conversion of uranyl into studtite for uranium extraction - Huazhen Rong; Handan Wen; Jiashun Mao; Yue Ma; Xiaohui Yan; Min Luo; Tao Liu; Yihui Yuan; Ning Wang (Desalination, 2026)

Robust retrieval of inland water nitrogen and phosphorus: De-biasing satellite-in situ matchups and integrating environmental constraints - Xihua Wang; Xingyu Zhu; Y. Jun Xu; Yongjiu Feng; Rong Huang; Chenyi Shi; Chengming Luo; Boyang Mao; Shunqing Jia; Qinya Lv; Zejun Liu; Xuming Ji; et al. (Journal of Water Process Engineering, 2026)

Intensive anthropogenic activities control the spatiotemporal heterogeneity of river eutrophication at the watershed scale - Xihua Wang; Shunqing Jia; Y. Jun Xu; Chaomeng Dai; Nianqing Zhou; Zejun Liu; Boyang Mao; Qinya Lv; Xuming Ji; Chengming Luo; Yan Dai; Yanxin Rong (Journal of Hydrology, 2026)

Microenvironment-regulated Fe single-atom nanozyme with neutral-pH peroxidase-mimicking activity for paper-based multiplexed biomarker detection - Rong Huang; Linping Tian; Dongmei Deng; Xiaoxia Yan; Haibo He; Wei Wang; Liqiang Luo (Analytica Chimica Acta, 2026)

Differential effects of alcohol-derived serum metabolites and direct ethanol exposure on mouse preantral follicle development - Meng-Ting Cao; Yang Shi; Chun Li; Yi-Lin Fan; Zhu-Rong Hu; Le-Ning Dang; Xue-Rui He; Wei-Qiang Luo; Jing-Jing Li; Xing-Rong Yan (Chemico-Biological Interactions, 2026)

Effects of Poly-γ-Glutamic Acid Application on Greenhouse Gas Emissions and GrainYield Under Different Direct-Seeding Methods in Paddy Rice - Rong Huang; Shi-hao Li; Hong-yan Li; Qian Luo; Yu-quan Fu; Qu-chen Zhou; Xiang-yu Huang; Xue-zhu Du; Feng Sheng (Journal of Soil Science and Plant Nutrition, 2026)

Burkholderia cepacia NB-13: Biocontrol efficacy and medium-driven metabolic regulation - Zhou Yin; Xiaoqin Li; He Guan; Dindi Tu; Xingyi Luo; Wancheng Hu; Fanqian Zhou; Menglong Li; Shulin Liu; Hui Li; Rong Song; Kailin Liu; et al. (Pesticide Biochemistry and Physiology, 2026)

Impacts of trunk height, tree planting density, and wall heating on flow and pollutant dispersion inside an urban street canyon - Yuan-Dong Huang; Yan-Jiao Jiang; Rong Ji; Ke-Xin Wang; Meng-Xin Chai; Yang Luo; Peng-Yi Cui (Environmental Fluid Mechanics, 2026)

Bionic platelet membrane-coated rutin nanoparticles attenuate ulcerative colitis by suppressing platelet-mediated macrophage inflammation - Rong Zhang; Ruya Mei; Bingqing Liang; Xinyue Zhang; Tong Zhang; Jie Luo; Juhua Zhang; Qin Pan; Yuzhong Yan (Drug Delivery and Translational Research, 2026)

Microbial lifestyles driven by C: N stoichiometric imbalance govern responses of carbon metabolism to nitrogen addition - Bo Kang; Rong Huang; Xun Yan; Linkang Chen; Shanghong Chen; Youlin Luo; Xiaoyan Tang; Yingjie Wu; Qi Tao; Qiang Xu; Changquan Wang; Bing Li (Soil Biology and Biochemistry, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Enhanced tellurium recovery via ultrasonic-assisted alkaline leaching-electrodeposition with integrated alkali regeneration - Su Yan; Shixing Wang; Libo Zhang; Rong Zhu; Xinrui Yang; Hongliang Liu; Jianqiang Ye; Guowei Luo; Yonggang Zuo; Gengwei Zhang; Guo Lin; Likang Fu (Chemical Engineering Journal, 2026)

Elevated CO2 accelerates mineral-protected organic carbon loss in the upland rhizosphere after paddy drainage - Xun Yan; Zhifan Li; Bo Kang; Tao Li; Linkang Chen; Junwen Zhao; Bing Li; Youlin Luo; Yingjie Wu; Rong Huang; Xiaoyan Tang; Qiang Xu; et al. (CATENA, 2026)

Operational control mechanism and pilot-scale demonstration of integrated fixed-film activated sludge partial nitritation/anammox system - Zibin Luo; Chao Rong; Tianjie Wang; Yu Qin; Jiang Wu; Yan Guo; Yisong Hu; Zhe Kong; Taira Hanaoka; Shinichi Sakemi; Yu-You Li (Bioresource Technology, 2026)

Hybrid prediction framework for total nitrogen in freshwater lake watershed based on the northern goshawk optimization and multiple machine learning methods: An integrated strategy from data cleaning to model optimization - Xihua Wang; Chengming Luo; Y. Jun Xu; Shunqing Jia; Zejun Liu; Boyang Mao; Yan Dai; Yanxin Rong; Qinya Lv; Xuming Ji (Journal of Environmental Chemical Engineering, 2026)

Precise pH control and synergistic interaction of raw materials improve the quality of stewed beef: multi-omics analysis of tenderization mechanisms and flavor restructuring - Yan Shen; Zezhu Du; Jinya Dong; Yuanfeng Chen; Huiqing Luo; Siyu Zhou; Cheng Gong; Shikuan Zhao; Zhiyu Li; Lihui Yu; Rong Geng; Xiaocui Du; et al. (Food Chemistry, 2026)

Coupled in-situ H2O2 generation and utilization over donor-acceptor covalent organic frameworks for rapid photocatalytic U(VI) removal - Huazhen Rong; Jiashun Mao; Yue Ma; Xiaohui Yan; Min Luo; Handan Wen; Tao Liu; Yihui Yuan; Ning Wang (Desalination, 2026)

Pharmaceutical-dominated organic contaminants in plateau lakes: Suspect and non-target screening, PBT risk, and structure-based risk markers - Liben Chou; Wanshu Zhu; Rong Zhang; Jinsha Jin; Kai Huang; Lu Dong; Mengke Jin; Wenrui Luo; Yan Mao; Xiangyi Yu; Haoyue Tan; Jing Guo; et al. (Water Research, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

New mechanistic insights into the antiviral candidate CA-P: Activation of plant redox-mediated defense and suppression of virus biosynthesis - Rong-Shuang Luo; Yan-Wei Huang; Yu-Cheng Gu; Long Cheng; Wu-Bin Shao; Yan-Mei Liao; Qian Guo; Dan Zeng; Hong-Mei Xiang; Xiang Zhou; Li-Wei Liu; Zhi-Bing Wu; et al. (Pesticide Biochemistry and Physiology, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

Trichoderma maomingense (Sordariomycetes, Hypocreaceae), a New Species Isolated From Bamboo in Guangdong Province, China - Dai‐Yan Huang; Qiu‐Rong Huang; Zhang‐Yong Dong; Mei Luo (New Zealand Journal of Botany, 2026)
Trichoderma species are widely distributed across various habitats worldwide and play significant roles in the biological control of plant diseases, plant growth promotion, and soil improvement. In this study, a novel Trichoderma species was isolated from dead culms of Bambusa cerosissima McClure in Maoming City, Guangdong Province, China. Based on morphological characteristics and multigene phylogenetic analyses of translation elongation factor 1 α ( tef1‐α ), nuclear internal transcribed spacer of rDNA region (ITS), and RNA polymerase second largest subunit ( rpb2 ) by both maximum likelihood (ML) and bayesian inference (BI) approaches, three isolates were identified as a new species within the Koningii‐clade, named Trichoderma maomingense sp. nov. The distinctions between this new species and its closely related taxa are discussed in detail.

Intensive anthropogenic activities drive dynamic surface water-groundwater interactions: Implications for contaminant pathways at a catchment scale - Shunqing Jia; Xihua Wang; Y. Jun Xu; Chaomeng Dai; Nianqing Zhou; Zejun Liu; Boyang Mao; Qinya Lv; Xuming Ji; Chengming Luo; Yan Dai; Yanxin Rong (Journal of Contaminant Hydrology, 2026)

Deciphering runoff-sediment-nutrient dynamics in agricultural watersheds supplied by large feeder Rivers: A multi-scale analysis - Xihua Wang; Xuming Ji; Y. Jun Xu; Boyang Mao; Shunqing Jia; Zejun Liu; Qinya Lv; Chengming Luo; Yan Dai; Yanxin Rong (Journal of Contaminant Hydrology, 2026)

Divergence in anthropogenic activities contributed to the eutrophication heterogeneity between river and lake at basin scale: new insights from trophic state index in Asia's largest basin (Yangtze River) - Yan Dai; Xihua Wang; Y. Jun Xu; Qinya Lv; Xuming Ji; Boyang Mao; Shunqing Jia; Zejun Liu; Chengming Luo; Yanxin Rong (Journal of Contaminant Hydrology, 2026)

Prediction of ammonia and total nitrogen in large freshwater lake watershed based on small sample data and analysis of their spatiotemporal variation and driving mechanism - Chengming Luo; Xihua Wang; Y. Jun Xu; Shunqing Jia; Zejun Liu; Boyang Mao; Qinya Lv; Xuming Ji; Yanxin Rong; Yan Dai (Process Safety and Environmental Protection, 2025)

Hypocalcemia as biological mechanism responsible for prenatal exposure to polycyclic aromatic hydrocarbons (PAHs) and anemia: Insights from Zunyi birth cohort - Lei Luo; Wenbi Yang; Haonan Zhang; Lei Bai; Zhongbao Chen; Lin Tao; Haiyan Wang; Shimin Xiong; Ruoxuan Li; Yijun Liu; Xingyan Liu; Yan Xie; et al. (Journal of Environmental Sciences, 2025)

Unraveling nitrogen evolution characteristics and driving mechanisms of estuarine alluvial islands - Xihua Wang; Yanxin Rong; Y. Jun Xu; Qinya lv; Xuming Ji; Boyang Mao; Shunqing Jia; Zejun Liu; Chengming Luo; Yan Dai (Journal of Contaminant Hydrology, 2025)

Layered manure enhances root development via soil hydrothermal optimization in ridge tillage - Bo Kang; Xun Yan; Yingjie Zhang; Rong Huang; Youlin Luo; Qiang Xu; Lihong Han; Changquan Wang; Bing Li (Plant and Soil, 2025)

Biotransformation causes the sex-specific regulation of polychlorinated biphenyls during metamorphosis of silkworm (Bombyx mori) and their effect on the silkworm development - Xue-Meng Qi; Xiao-Jun Luo; Pei-Xin Su; Peng-Peng Chen; Qing-Rong Yang; Yan-Hong Zeng; Bi-Xian Mai (Journal of Hazardous Materials, 2025)

Unveiling the mystery of eutrophication prediction for large freshwater lake through Temporal Convolutional Network hybrid model - Chengming Luo; Xihua Wang; Y. Jun Xu; Shunqing Jia; Zejun Liu; Boyang Mao; Yan Dai; Yanxin Rong; Qinya Lv; Xuming Ji (Journal of Environmental Chemical Engineering, 2025)

Hyperoside extends lifespan in Caenorhabditis elegans through SEK-1/PMK-1/SKN-1 pathway - Xin-Tian Yu; Lin Shi; Qiong Huang; Bao Li; Yan-Qing Li; Li-Lan Ou; Huai-Rong Luo; Gui-Sheng Wu (Biogerontology, 2025)

Impact of intensive human activities on nitrate pollution in river basins: A spatiotemporal isotopic analysis - Shunqing Jia; Xihua Wang; Y. Jun Xu; Zejun Liu; Boyang Mao; Qinya Lv; Xuming Ji; Chengming Luo; Yan Dai; Yanxin Rong (Journal of Water Process Engineering, 2025)

Dual-quantification of the different contributions of climate change and anthropogenic activities to eutrophication of rivers and lakes in Asia's largest river basin (Yangtze River) - Xihua Wang; Yan Dai; Y. Jun Xu; Qinya Lv; Xuming Ji; Boyang Mao; Shunqing Jia; Zejun Liu; Chengming Luo; Yanxin Rong (Journal of Hazardous Materials, 2025)

Nanoplastics under the charge effects: Unveiling the potential threats to amphibian (Rana nigromaculata) growth, intestinal damage and microbial ecology - Peng Fang; Shuzi Ye; Zidie Luo; Rong Guo; Yan Jiang; Lemei Liu; Siwen Li; Fang Xiao (Environmental Pollution, 2025)

Bio-organic fertilizer application improves cucumber growth, disease resistance, and soil fertility by regulating rhizosphere microbiomes - Junyan Yang; Xin Liu; Xiangmin Rong; Pan Jiang; Yixiang Xia; Guixian Xie; Gongwen Luo; Xiaoyuan Yan (Plant and Soil, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Ultra-sensitive, versatile and portable detection of hydrazine in eco-environmental systems using a smartphone-integrated ratiometric fluorescent sensor - Xiao-Hong Li; Meng-Zhao Li; Xiao-Yan Yang; Tian-Yan Wang; Yin-Heng Luo; WMWW Kandegama; Jing-Yi Li; Ge-Fei Hao; Chun-Rong Liu (Journal of Hazardous Materials, 2025)

Multi-machine learning methods for rapid and synergistic inversion of groundwater contamination source, hydrogeologic parameter and boundary condition - Chengming Luo; Xihua Wang; Y. Jun Xu; Qinya Lv; Xuming Ji; Boyang Mao; Shunqing Jia; Zejun Liu; Yanxin Rong; Yan Dai (Journal of Contaminant Hydrology, 2025)

PtBi nanocatalysts with controlled chain-like structure and composition: Solvothermal synthesis and ethanol oxidation performance - Luo-Yi Yan; Han-Tao Zhang; Xiao-Yu Lu; Li-Ming Liu; Rong-Hua Zhang; Zheng Cheng; Shuai-Wei Fan; Xin-Wen Zhou (Fuel, 2025)

Screening novel anti-inflammatory peptides inhibiting the NLRP3 inflammasome from UHPLC-MS/MS-characterized peptide profiles of cocoa tea protein hydrolysates - Hai-Biao Gong; Chang-Yu Yan; Hui-Er Ye; Shuo-Yan Tan; Shi-Sheng Chen; Jian-Wen Ye; Wan-Yang Sun; Hong-Li Tan; Xiang Luo; Jie Niu; Kun Li; Jing-Hao Wang; et al. (Food Research International, 2025)

Spatiotemporal analysis of microclimatic and environmental interactions with visualcompensation for thermalcomfort: Case studies in Hangzhou's urban waterfronts - Rong Xia; Zhixing Li; Xiaowen Gao; Siyi Luo; Ruiyin Xiong; Xuzhong Yan (Urban Climate, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

SIRT5: a potential target for discovering bioactive natural products - Yuwei Xie; Nali Cai; Xiaohua Liu; Liangliang He; Yiming Ma; Changyu Yan; Juan Liang; Shu-Hua Ouyang; Ao Luo; Yingzhi He; Jun Lu; Dang Ao; et al. (Journal of Natural Medicines, 2025)
Silent information regulator 5 (SIRT5) is the fifth member of the sirtuin family, which is mainly expressed in mitochondrial matrix. SIRT5 plays a key role in metabolism and antioxidant responses, and is an important regulator for maintaining intracellular homeostasis. Given its involvement in multiple cellular processes, dysregulation of SIRT5 activity is associated with a variety of diseases. This review explores the structural characteristics of SIRT5 that influence its substrate specificity, highlights recent research advances, and summarizes its four key enzymatic activities along with their corresponding substrates in disease contexts. We also discuss the natural products that modulate SIRT5 activity and identify potential targets of SIRT5 through virtual docking, which may provide new therapeutic avenues. Although the mechanism of SIRT5 in diseases needs to be further elucidated and deglutathionylation activities are still at an early stage, targeting SIRT5 and its substrates holds significant promise for the development of novel therapeutics. Graphical abstract

The study of the response regularity of photosynthesis to flash drought in different vegetation ecosystems of the middle and lower reaches of the Yangtze River Basin - Yunjun Zhan; Chuanqi Ma; Yan Yan; Yongsi Luo; Xueting Wang; Senrong Wang; Yuejing Rong (International Journal of Biometeorology, 2025)

Isolation and genomic characterization of multi-drug resistant Morganella morganii strain from Chinese Soft-Shell Turtle Pelodiscus sinensis - Rong-Hua Wang; Meng-Lu Yan; Qing Tan; Jin-Long Wang; Yu-Shuang Luo; Zhong-Yuan Chen (Aquaculture, 2025)

Combining POA-VMD for multi-machine learning methods to predict ammonia nitrogen in the largest freshwater lake in China (Poyang Lake) - Chengming Luo; Xihua Wang; Y. Jun Xu; Cong Wang; Qinya Lv; Xuming Ji; Boyang Mao; Shunqing Jia; Zejun Liu; Yanxin Rong; Yan Dai (Journal of Water Process Engineering, 2025)

Occurrence and distribution of PAHs in the Yangtze River and urban river waters of Nanjing, China: Insights from in situ DGT measurements - Qiuyu Rong; Hao Zhang; Yanying Li; Liying Yan; Jun Luo; Kevin C. Jones (Environmental Pollution, 2025)

Construction of phenothiazine-decorated ZnO quantum dots with intelligent response to bacterial pH/amidase microenvironment for inducing bacterial ferroptosis-like death - Wu-Bin Shao; Rong-Shuang Luo; Yan-Wei Huang; Long Cheng; Dan Zeng; Xiang Zhou; Li-Wei Liu; Song Yang (Chemical Engineering Journal, 2025)

The diverse sleep structure of mid-day nap in college students - Qin Xiao; Xueqi Sun; Guoxin Zeng; Xin Luo; Qian Jiang; Rong Ren; Xiangdong Tang; Chao He; Zhian Hu; Fenlan Luo; Jie Yan (Sleep and Biological Rhythms, 2025)

Accumulation of lipophilic and proteinophilic halogenated organic pollutants (HOPs) in the different types of feathers of laying hens - Xi Chen; Xiao-Jun Luo; Qun-Jie Feng; Yu Liu; Jun-Zhe Dai; Peng-Peng Chen; Pei-Xin Su; Qing-Rong Yang; Yan-Hong Zeng; Bi-Xian Mai (Journal of Hazardous Materials, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Transcriptome Sequencing Reveals Effects of Artificial Feed Domestication on Intestinal Performance and Gene Expression of Carnivorous Mandarin Fish (Siniperca chuatsi) and Related Mechanisms - Jia-Xing Luo; Xiao-Tian Gao; Zhen Rong; Li-Han Zhang; Yan-Feng Sun; Zun-Li Qi; Qi Yu; Khor Waiho; Wei-Xu Zhao; Yi-Huan Xu; Chun-Long Zhao; Cheng-Bin Wu (Marine Biotechnology, 2025)

Model-based analysis for investigating the impact of tumor size, lymphocyte and neutrophil on the survival of breast cancer 4T1 tumor-bearing mice - Qing-yu Yao; Xin-yu Hou; Wei-zhe Jian; Tian-yu Wang; Ping-yao Luo; Jun-sheng Xue; Rong Chen; Tian-yan Zhou (Toxicology and Applied Pharmacology, 2025)

Structurally diversified sesquiterpenoids from Chloranthus henryi and their neuroprotective activities on H2O2 damaged PC12 cells - Meng-Li He; Lian-Lian Xu; Yang Liu; Yan-Ping Gao; Yong-Ming Luo; Rong-Cai Yue; Fang-You Chen (Phytochemistry, 2025)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

An origami microfluidic paper device based on core-shell Cu@Cu2S@N-doped carbon hollow nanocubes - Yuanyuan Li; Huinan Chen; Rong Huang; Dongmei Deng; Xiaoxia Yan; Liqiang Luo (Analytica Chimica Acta, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Draft Genome Sequence of Candida saopaulonensis from a Very Premature Infant with Sepsis - Ya-Ting Ning; Rong-Chen Dai; Zheng-Yu Luo; Meng Xiao; Yingchun Xu; Qun Yan; Li Zhang (Mycopathologia, 2024)
The rare fungus Candida saopaulonensis has never been reported to be associated with human infection. We report the draft genome sequence of the first clinical isolate of C. saopaulonensis, which was isolated from a very premature infant with sepsis. This is the first genome assembly reaching the near-complete chromosomal level with structural annotation for this species, opening up avenues for exploring evolutionary patterns and genetic mechanisms of pathogenesis.

Development of a novel DGT passive sampler for measuring polycyclic aromatic hydrocarbons in aquatic systems - Qiuyu Rong; Yanying Li; Jun Luo; Liying Yan; Kevin C. Jones; Hao Zhang (Journal of Hazardous Materials, 2024)

Development and validation of an in situ high-resolution technique for measuring antibiotics in sediments - Yanying Li; Qiuyu Rong; Chao Han; Hanbing Li; Jun Luo; Liying Yan; Degao Wang; Kevin C. Jones; Hao Zhang (Journal of Hazardous Materials, 2024)

Study by means of 1H nuclear magnetic resonance of the oxidation process in high oleic sunflower oil and palm oil during deep-frying of fish cakes - Xiaoyu Luo; Benlun Hu; Caihua Jia; Ru Liu; Jianhua Rong; Siming Zhao; Meng Niu; Yan Xu; Tao Yin; Juan You (Food Research International, 2024)

Research progress of main synthetic catalysts used in biomass pyrolysis - Hongwei Rong; Penghong He; Yuxin Luo; Haizhen Cai; Mahmood Laghari; Dabin Guo; Yan Ren; Baihui Cui (Process Safety and Environmental Protection, 2023)

Efficacy of pterostilbene suppression on Aspergillus flavus growth, aflatoxin B1 biosynthesis and potential mechanisms - Yong-Mei Hu; Yi-Rong Wang; Wen-Bin Zhao; Yan Yan Ding; Zheng-Rong Wu; Guang-Han Wang; Peng Deng; Shao-Yong Zhang; Jun-Xia An; Zhi-Jun Zhang; Xiong-Fei Luo; Ying-Qian Liu (International Journal of Food Microbiology, 2023)

Two new triterpenoid saponins from Bupleurum marginatum Wall. ex DC - Ke Luo; Rong-Ji Dai; Zhi Wang; Yan-Bo Zeng; Yu-Lin Deng; Fang Lv (Natural Product Research, 2023)

Lack of the CCT domain changes the ability of mango MiCOL14A to resist salt and drought stress in Arabidopsis - Shu-Quan Chen; Cong Luo; Yuan Liu; Rong-Zhen Liang; Xing Huang; Ting-Ting Lu; Yi-Hang Guo; Ruo-Yan Li; Chu-Ting Huang; Zhuo Wang; Xin-Hua He (Plant Science, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Association of climatic variables with risk of transmission of influenza in Guangzhou, China, 2005–2021 - Rong Zhang; Ka Yan Lai; Wenhui Liu; Yanhui Liu; Wenfeng Cai; Chris Webster; Lei Luo; Chinmoy Sarkar (International Journal of Hygiene and Environmental Health, 2023)

Biochar amendments combined with organic fertilizer improve maize productivity and mitigate nutrient loss by regulating the C–N–P stoichiometry of soil, microbiome, and enzymes - Bojing Yan; Yuping Zhang; Yizhe Wang; Xiangmin Rong; Jianwei Peng; Jiangchi Fei; Gongwen Luo (Chemosphere, 2023)

Overexpression of Sedum SpHMA2, SpHMA3 and SpNramp6 in Brassica napus increases multiple heavy metals accumulation for phytoextraction - Zi Yang; Hai-Tao Wu; Hao Yang; Wan-Di Chen; Jia-Lan Liu; Fan Yang; Li Tai; Bin-Bin Li; Bo Yuan; Wen-Ting Liu; Yan-Feng Zhang; Yan-Rong Luo; et al. (Journal of Hazardous Materials, 2023)

The phosphorus harvest from low-temperature mainstream wastewater through iron phosphate crystallization in a pilot-scale partial nitritation/anammox reactor - Yan Guo; Eli Hendrik Sanjaya; Tianjie Wang; Chao Rong; Zibin Luo; Yi Xue; Hong Chen; Yu-You Li (Science of The Total Environment, 2023)

Degradation of antibiotics by electrochemical advanced oxidation processes (EAOPs): Performance, mechanisms, and perspectives - Qingbin Yuan; Siyao Qu; Rong Li; Zheng-Yang Huo; Yan Gao; Yi Luo (Science of The Total Environment, 2023)

Efficient synthesis of PdIr nanocatalysts with controllable surface composition for electrochemical oxidation of methanol - Ce Fu; Pan Wang; Rong-Hua Zhang; Luo-Yi Yan; Zheng Cheng; Xin Zhang; Xin-Wen Zhou (Fuel, 2023)

Assessing the Impact of Atrazine on the Availability of Arsenic in Soils Using DGT Technique - Yanying Li; Liying Yan; Qiuyu Rong; Jun Luo; Hao Zhang; Kevin C. Jones (Bulletin of Environmental Contamination and Toxicology, 2022)

Composition, Demographic History, and Population Structures of Trichiurus - Kui-Ching Hsu; Mu-Rong Yi; Sui Gu; Xiong-Bo He; Zhi-Sen Luo; Bin Kang; Hung-Du Lin; Yun-Rong Yan (Frontiers in Marine Science, 2022)
Sequences of the complete mitochondrial cytochrome oxidase subunit I gene were used to identify Trichiurus species and examine their population genetic structure and demographic history along the coast of China. Three Trichiurus species were found. Trichiurus japonicus lives in colder waters along the continental shelves in the China Seas, while Trichiurus nanhaiensis lives warmer waters along continental slopes in the South China Sea, and Trichiurus brevis lives in shallow and warmer waters in the South China Sea. The migrations of these species were mainly associated with feeding and spawning preferences. Two major wintering and spawning grounds in the East China Sea and South China Sea were found. All species showed a lack of population genetic structure resulting from their oceanodromous life cycle (the degree of population substructure index N ST = 0.000–0.149), but the results of approximate Bayesian computational approaches suggested population declines or stabilization and differentiation. The results of the T MRCA (time to the most recent common ancestor) showed that during glaciations, the Yellow Sea and the East China Sea were completely exposed, and the South China Sea acted as a refugium. Thus, the populations of these three species experienced differentiation during glaciations. This study also examined the limitations of Bayesian skyline plot analysis.

Does the institutional environment influence corporate social responsibility? Consideration of green investment of enterprises—evidence from China - Shu-Rong Han; Pei Li; Jian-Jun Xiang; Xiang-Hua Luo; Chun-Yan Chen (Environmental Science and Pollution Research, 2022)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Noroleanane-type triterpenoids from Dolichos trilobus L. and their anti-α-glucosidase activities - Ming Luo; Yan-Hong Li; Ya Lu; Yan Yuan; Rong-Sheng Ruan; Yong-Ming Chuan; Kai Tian; Xiang-Zhong Huang (Natural Product Research, 2021)

Identification and Phylogenetic Analysis of Xanthomonas albilineans (Ashby) Dowson Based on Multiple Gene Sequences in Yunnan Province, China - Rong-Yue Zhang; Xiao-Yan Wang; Hong-Li Shan; Jie Li; Wen-Feng Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin; Ying-Kun Huang (Sugar Tech, 2019)

Molecular Identification of Sugarcane White Leaf in Puer, Yunnan Province, China - Rong-Yue Zhang; Wen-Feng Li; Ying-Kun Huang; Xiao-Yan Wang; Hong-Li Shan; Jie Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin (Sugar Tech, 2019)

Developing genetically segregating populations for localization of novel sugarcane brown rust resistance genes - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Hong-Li Shan; Rong-Yue Zhang; Jie Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin (Euphytica, 2019)

Identification and Evaluation of Resistance to Sugarcane Streak Mosaic Virus (SCSMV) and Sorghum Mosaic Virus (SrMV) in Excellent Sugarcane Innovation Germplasms in China - Wen-Feng Li; Hong-Li Shan; Xiao-Yan Cang; Xin Lu; Rong-Yue Zhang; Xiao-Yan Wang; Jiong Yin; Zhi-Ming Luo; Ying-Kun Huang (Sugar Tech, 2019)

Field Resistance of Different Sugarcane Varieties to Sugarcane Thrips (Fulmekiola serratus) in China - Zhi-Ming Luo; Xiao-Yan Wang; Ying-Kun Huang; Rong-Yue Zhang; Wen-Feng Li; Hong-Li Shan; Xiao-Yan Cang; Jie Li; Jiong Yin (Sugar Tech, 2019)

In Vitro Susceptibility of Berberine Combined with Antifungal Agents Against the Yeast Form of Talaromyces marneffei - Hong Luo; Kai-su Pan; Xiao-lu Luo; Dong-yan Zheng; Alex Andrianopoulos; Le-min Wen; Yan-qing Zheng; Jing Guo; Chun-yang Huang; Xiu-ying Li; Rong Hu; Yu-jiao Li; et al. (Mycopathologia, 2019)

Reduced thiamine binding is a novel mechanism for TPK deficiency disorder - Wenjie Huang; Jiao Qin; Dingdong Liu; Yan Wang; Xiaofei Shen; Na Yang; Hui Zhou; Xiao-Tang Cai; Zhi-Ling Wang; Dan Yu; Rong Luo; Qingxiang Sun; et al. (Molecular Genetics and Genomics, 2019)

A new actinomycin Z analogue with an additional oxygen bridge between chromophore and β -depsipentapeptide from Streptomyces sp. KIB-H714 - Miao Dong; Pei Cao; Ya-Tuan Ma; Jianying Luo; Yijun Yan; Rong-Tao Li; Sheng-Xiong Huang (Natural Product Research, 2019)

Neuroinflammation in acute hepatic encephalopathy rats: imaging and therapeutic effectiveness evaluation using 11C-PK11195 and 18F-DPA-714 micro-positron emission tomography - Song Luo; Xiang Kong; Jin Rong Wu; Chun Yan Wang; Ying Tian; Gang Zheng; Yun Yan Su; Guang Ming Lu; Long Jiang Zhang; Gui Fen Yang (Metabolic Brain Disease, 2018)

Kinematic Outcome Measures using Target-Reaching Arm Movement in Stroke - Qianqian Yang; Yuan Yang; Jie Luo; Le Li; Tiebin Yan; Rong Song (Annals of Biomedical Engineering, 2017)

Changes in the Intestinal Microbiota of Gibel Carp (Carassius gibelio) Associated with Cyprinid herpesvirus 2 (CyHV-2) Infection - Rong She; Tong-Tong Li; Dan Luo; Jia-Bao Li; Liu-Yi Yin; Huan Li; Yao-Min Liu; Xiang-Zhen Li; Qi-gui Yan (Current Microbiology, 2017)

Molecular detection and phylogenetic analysis of viruses causing mosaic symptoms in new sugarcane varieties in China - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Jiong Yin; Zhi-Ming Luo (European Journal of Plant Pathology, 2017)

Globular adiponectin inhibits leptin-stimulated esophageal adenocarcinoma cell proliferation via adiponectin receptor 2-mediated suppression of UHRF1 - Jun Wang; Yan Cheng; Xiaoran Yin; Jie Wu; Yumei Luo; Jing Wu; Jia Di; Dong Liu; Yahui Huang; Rong Zhang; Jun Zhang (Molecular and Cellular Biochemistry, 2017)

Molecular Detection of Bru1 Gene and Identification of Brown Rust Resistance in Chinese Sugarcane Germplasm - Wen-Feng Li; Xiao-Yan Wang; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Jiong Yin; Zhi-Ming Luo (Sugar Tech, 2017)

Chryseobacterium chengduensis sp. nov. isolated from the air of captive giant panda enclosures in Chengdu, China - Cai-fang Wen; Li-xin Xi; Shan Zhao; Zhong-xiang Hao; Lu Luo; Hong Liao; Zhen-rong Chen; Rong She; Guo-quan Han; San-jie Cao; Rui Wu; Qi-gui Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

Preparation of Bacterial Cellulose/Inorganic Gel of Bentonite Composite by In Situ Modification - Bo Wang; Gao-xiang Qi; Chao Huang; Xiao-Yan Yang; Hai-Rong Zhang; Jun Luo; Xue-Fang Chen; Lian Xiong; Xin-De Chen (Indian Journal of Microbiology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Lysobacter chengduensis sp. nov. Isolated from the Air of Captive Ailuropoda melanoleuca Enclosures in Chengdu, China - Caifang Wen; Lixin Xi; Rong She; Shan Zhao; Zhongxiang Hao; Lu Luo; Hong Liao; Zhenrong Chen; Guoquan Han; Sanjie Cao; Rui Wu; Qigui Yan; et al. (Current Microbiology, 2016)

Corilagin Protects Against HSV1 Encephalitis Through Inhibiting the TLR2 Signaling Pathways In Vivo and In Vitro - Yuan-Jin Guo; Tao Luo; Fei Wu; Huan Liu; Hua-Rong Li; Yuan-Wu Mei; Shu-Ling Zhang; Jun-Yan Tao; Ji-Hua Dong; Yuan Fang; Lei Zhao (Molecular Neurobiology, 2015)

Zinc binds to and directly inhibits protein phosphatase 2A in vitro - Yan Xiong; Dan-Ju Luo; Xiu-Lian Wang; Mei Qiu; Yang Yang; Xiong Yan; Jian-Zhi Wang; Qi-Fa Ye; Rong Liu (Neuroscience Bulletin, 2015)

Identification of Sugarcane White Leaf Phytoplasma in Fields and Quaratine Sugarcane Samples in Yunnan Province, China - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Zhi-Ming Luo; Jiong Yin; Ke Shen (Sugar Tech, 2015)

Characterization of the biological properties and complete genome sequence analysis of a cattle-derived rabies virus isolate from the Guangxi province of southern China - Hai-Bo Tang; Zhuan-Ling Lu; Yi-Zhi Zhong; Xiao-Xia He; Tao-Zhen Zhong; Yan Pan; Xian-Kai Wei; Yang Luo; Su-Huan Liao; Nobuyuki Minamoto; Ting Rong Luo (Virus Genes, 2014)

Application of Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration in the Management of Mediastinal and Hilar Lymphadenopathy Without Intrapulmonary Mass: Experience from the Largest Cancer Center of Southern China - Guang-yu Luo; Pei-qiang Cai; Jie-hua He; Jian-jun Li; Yin Li; Hong-bo Shan; Rong Zhang; Xiao-yan Gao; Xiang-ming Lao; Guo-liang Xu (Cell Biochemistry and Biophysics, 2013)

Identification of differentially expressed genes in Brassica juncea var. tumida Tsen following infection by Plasmodiophora brassicae - Yuanli Luo; Youping Yin; Yan Liu; Xiaotu Pei; Zhongkang Wang; Yonghong Fan; Xuyi Wang; Rong Leng (European Journal of Plant Pathology, 2013)

Lyssavirus surveillance in bats of southern China’s Guangxi Province - Zhuan-Ling Lu; Wen Wang; Wei-Li Yin; Hai-Bo Tang; Yan Pan; Xiang Liang; Qi Liu; Yi Xiong; Nobuyuki Minamoto; Ting Rong Luo (Virus Genes, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

Rice choline monooxygenase (OsCMO) protein functions in enhancing glycine betaine biosynthesis in transgenic tobacco but does not accumulate in rice (Oryza sativa L. ssp. japonica) - Di Luo; Xiangli Niu; Jinde Yu; Jun Yan; Xiaojun Gou; Bao-Rong Lu; Yongsheng Liu (Plant Cell Reports, 2012)

Impact of nodular size on the predictive values of gray-scale, color-Doppler ultrasound, and sonoelastography for assessment of thyroid nodules - Yu-rong Hong; Yu-lian Wu; Zhi-yan Luo; Ning-bo Wu; Xue-ming Liu (Journal of Zhejiang University-SCIENCE B, 2012)

Expression of ethylene response genes during persimmon fruit astringency removal - Xue-ren Yin; Yan-na Shi; Ting Min; Zheng-rong Luo; Yun-cong Yao; Qian Xu; Ian Ferguson; Kun-song Chen (Planta, 2012)

Genetic diversity analysis of Rhododendron aureum Georgi (Ericaceae) located on Changbai Mountain using ISSR and RAPD markers - Yan-Fei Liu; Ming Xing; Wei Zhao; Rong-Jun Fan; Su Luo; Xia Chen (Plant Systematics and Evolution, 2012)

HIV-infection resistance in PMBC-derived dendritic cells modified with recombinant virus - Cheng-lai Xia; Ping Zhu; Yan-tao Cai; Guang-bin Zhu; Zheng-rong Mei; Hanhui Huang; Di-xian Luo; Peng-ke Yan (Archives of Virology, 2012)

Downregulation of OsPK1, a cytosolic pyruvate kinase, by T-DNA insertion causes dwarfism and panicle enclosure in rice - Yan Zhang; Wenkai Xiao; Lijuan Luo; Jinhuan Pang; Wei Rong; Chaozu He (Planta, 2012)

The complete mitochondrial genome of Spilonota lechriaspis Meyrick (Lepidoptera: Tortricidae) - Jin-Liang Zhao; Yan-Yan Zhang; A-Rong Luo; Guo-Fang Jiang; Stephen L. Cameron; Chao-Dong Zhu (Molecular Biology Reports, 2011)

Predominance of Precipitation and Temperature Controls on Ecosystem CO2 Exchange in Zoige Alpine Wetlands of Southwest China - Yan Bin Hao; Xiao Yong Cui; Yan Fen Wang; Xu Rong Mei; Xiao Ming Kang; Ning Wu; Peng Luo; Dan Zhu (Wetlands, 2011)

Interaction of MT1-MMP and laminin-5γ2 chain correlates with metastasis and invasiveness in human esophageal squamous cell carcinoma - Xiao-Ming Shen; Yu-Peng Wu; Yan-Bin Feng; Man-Li Luo; Xiao-Li Du; Yu Zhang; Yan Cai; Xin Xu; Ya-Ling Han; Xun Zhang; Qi-Min Zhan; Ming-Rong Wang (Clinical & Experimental Metastasis, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)